Being a person with disabilities or experiencing disability: Two perspectives on the social response to disability - Jerome Bickenbach; Sara Rubinelli; Gerold Stucki (Medical Journals Sweden, 2017)
Disability has a profound impact, both on those who live with it and on society that responds to the needs of people experiencing disability. Society has a primary obligation to respond to the impact of disability. Rehabilitation has an essential role to play here; but its relationship to disability embodies a broader social ambiguity about what it means to experience disability. On the one hand, disability is a mark of a minority group persons with disabilities, which has, historically, been socially disadvantaged. On the other, disability is a matter of how health conditions and associated impairments interact with the physical and social world to create limits on what people can do or become. However, just as health problems are universal over the life course, so too is disability. Everyone experiences disability. This paper explores the historical underpinnings of these two perspectives on disability, in particular how they impact on rehabilitation practice and policy. After surveying the social consequences of these perspectives, the paper attempts to reconcile them in order to enhance the overall effectiveness and relevance of the social response to disability.